The influence of e-wom and security on cryptocurrency purchase decisions in generation z through trust as mediation variables - Julhuda Julhuda; M. Irfani Hendri; Wenny Pebrianti; Maria Christiana Iman Kalis; Yulyanti Fahruna (Institute of Computer Science (IOCS), 2023)
Generation Z is a demographic group that has grown up with digital technology and has an important role in the adoption of cryptocurrency as an increasingly popular form of investment and online transactions. The advantages and potential of cryptocurrencies are attractive. However, several challenges need to be overcome, such as security issues, concerns about fake news, unclear regulations, and price volatility that will affect cryptocurrency purchasing decisions. This research aims to test whether factors such as the influence of Electronic Word of Mouth (eWOM), Security, and Trust influence cryptocurrency purchasing decisions in Generation Z. This research uses Structural Equation Modeling (SEM) and AMOS statistical tools. Data collection techniques were distributed through online questionnaires on the 5 largest islands in Indonesia with a sample of 200 respondents. The population of this research is Generation Z in the age range of 18-25 years, who are buyers of cryptocurrency using purposive sampling techniques. The results of this research show that electronic Word of Mouth has a positive and significant influence on cryptocurrency purchasing decisions in Generation Z. Perceptions of cryptocurrency security also have a significant influence on purchasing decisions. Trust is also an important factor in shaping Generation Z's Purchasing Decisions